Tingkat Kepuasan Konsumen dalam Menggunakan Smartphone Merek Xiaomi pada Mahasiswa Politeknik Negeri Bengkalis - Eko Darmawan; Suharyono Suharyono (Inovbiz: Jurnal Inovasi Bisnis, 2019)
A satisfication of customer is determined from customer perception on performance product or services to satisfy customer want. This research consign to knowing customer standard satisfy from using Xiaomi brand smarthphone of Bengkalis State Polytechnic Students. The type of research that use in this case as quantitative by spreading a questionner to 100 respondent people by using vote sample metode non "probability sampling with snowball sampling". The results of this research is showing that quality of product get  mean score 4,13, which is showing the standard of customer satisfy is high. A quality of services get mean score 3,92, which is showing the standard of customer  satisfy is high. Emotional get mean score 4,02, which is showing the standard of satisfy customer is high. The price get mean score 4,14 , which is showing the standard of satisfy customer is high. The cost and the easiness get mean score 4,15, which is showing the standard of satisfy customer is high. So, the most dominant factor on affect the standard of satisfy customer from using Xiaomi brand smartphone is a cost and easiness, mean while the factor who do not affect the most from the standard of satisfy customer from using Xiaomi brand smartphone is service quality.